The Relationship Between Emotional Intelligence And Academic Achievement Among Fourth-Grade Elementary School Students - Fitriayani Fitriayani; Ahmad Ahmad; Waode Ekadayanti (Journal of Education and Learning Sciences, 2025)
Emotional intelligence is an important internal factor that supports students' learning success by enabling them to recognize and regulate emotions, maintain self-motivation, and establish positive social relationships during the learning process. This study aimed to examine the relationship between emotional intelligence and academic achievement among fourth-grade students at SD Negeri 2 Konda, South Konawe Regency. A quantitative approach with a correlational research design was employed. The population and sample consisted of all 32 fourth-grade students, selected using a total sampling technique. Data on emotional intelligence were collected using a questionnaire, while academic achievement data were obtained from students' first-semester report-card grades. The data were analyzed using descriptive statistics and Pearson's Product-Moment correlation with the assistance of IBM SPSS. The results showed that the students' emotional intelligence and academic achievement were generally in the good category. Pearson's correlation analysis produced a correlation coefficient of r = 0.764 with a significance value of p < 0.001, indicating a strong, positive, and statistically significant relationship between emotional intelligence and academic achievement. The coefficient of determination (R²) was 0.583, indicating that emotional intelligence contributed 58.3% to the variation in students' academic achievement, while the remaining 41.7% was associated with other factors not examined in this study. Thus, higher emotional intelligence was associated with higher academic achievement among fourth-grade students at SD Negeri 2 Konda.